The Problem Of Neutral States In International Armed Conflicts - Kandi Kirana Larasati; Fera Wulandari Fajrin (Fakultas Hukum Universitas Widya Mataram, 2025)
This research was conducted because there was a legal conflict regarding the status of a neutral state whose actions did not conform to neutral values in the form of freezing the assets of citizens in banks located in neutral state. The formulation proposed in this study is: First, the concept of neutrality in contemporary international law armed conflicts. Second, legal consequences of the status of a neutral State in relation to international armed conflict. The purpose of this research is to outline the concept of neutrality and analyse the problem of a neutral country in the Russian-Ukrainian armed conflict. The research approach used is the Statute Approach, including the 1907 Hague Convention especially Convention V and Convention XIII and the Conceptual Approach, including Neutrality in Humanitarian Law and the Courant Normal.